2013
DOI: 10.1242/jcs.112623
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate Spt2 is a novel nucleolar histone chaperone that assists in ribosomal DNA transcription

Abstract: SummaryIn eukaryotes, transcription occurs in the chromatin context with the assistance of histone-binding proteins, such as chromatin/ nucleosome remodeling factors and histone chaperones. However, it is unclear how each remodeling factor or histone chaperone functions in transcription. Here, we identify a novel histone-binding protein, Spt2, in higher eukaryotes. Recombinant human Spt2 binds to histones and DNA, and promotes nucleosome assembly in vitro. Spt2 accumulates in nucleoli and interacts with RNA po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 60 publications
3
32
0
Order By: Relevance
“…Furthermore, The C terminus (571-685) of hSpt2, but not its N-terminal counterpart (1-570), bound His-tagged H3/H4 under low-salt conditions as monitored by pull-down assays (Osakabe et al 2013). We independently confirmed that the C terminus (571-685) of GST-tagged hSpt2 bound H3/H4 under low-salt conditions as monitored by pull-down assays (data not shown).…”
Section: Generation Of a Stable Hspt2c-h3/h4 Complexmentioning
confidence: 58%
See 4 more Smart Citations
“…Furthermore, The C terminus (571-685) of hSpt2, but not its N-terminal counterpart (1-570), bound His-tagged H3/H4 under low-salt conditions as monitored by pull-down assays (Osakabe et al 2013). We independently confirmed that the C terminus (571-685) of GST-tagged hSpt2 bound H3/H4 under low-salt conditions as monitored by pull-down assays (data not shown).…”
Section: Generation Of a Stable Hspt2c-h3/h4 Complexmentioning
confidence: 58%
“…Previous studies established that full-length hSpt2 bound to both H2A/H2B and H3/H4 under low-salt (0.15 M NaCl) conditions as monitored by gel shift assays (Osakabe et al 2013). Furthermore, The C terminus (571-685) of hSpt2, but not its N-terminal counterpart (1-570), bound His-tagged H3/H4 under low-salt conditions as monitored by pull-down assays (Osakabe et al 2013).…”
Section: Generation Of a Stable Hspt2c-h3/h4 Complexmentioning
confidence: 96%
See 3 more Smart Citations